Cylindrical Bounded Quaternion Control for Tracking and Surrounding a Ground Target Using UAVs⁎Research Supported by the Ministére de L'Education Nationale, de l'Enseignement Supérieur et de La Recherche, the National Network of Robotics Platforms (ROBOTEX), the Conseil Regional de Lorraine, from France, and the CONACYT from Mexico. Issue 2 (2020) - Abaunza, Hernan; Castillo, Pedro; Theilliol, Didier; Belkadi, Adel; Ciarletta, Laurent
Abstract: A cooperative tracking algorithm for multiple quadrotors autonomously tracking and surrounding a target ground vehicle is presented in this paper. A nonlinear bounded controller is proposed using geometrical functions to stabilize the translational and rotational dynamics using bounded 3-dimensional control inputs, employing quaternion properties and operators in its design, Lyapunov theory is used to prove system stability. The navigation challenge is tackled by proposing a cost function based on the desired behavior of the aerial vehicles for tracking and surrounding the target, which is solved by finding the optimal solution with a Particle Swarm Optimization algorithm. Simulations and experimental results corroborate the good performance of the scheme.